Thrombopoietin-Induced Signal Transduction and Potentiation of Platelet Activation - Oda, Atsushi; Miyakawa, Yoshitaka; Druker, Brian J.; Ozaki, Katsutoshi; Ohashi, Hideya; Kato, Takashi; Miyazaki, Hiroshi; Handa, Makoto; Ikebuchi, Kenji; Ikeda, Yasuo (Thrombosis and Haemostasis, 1999)
The presence of thrombopoietin, a humoral regulator of megakaryopoiesis and thrombopoiesis, had been suggested for years,1 however, some investigators were skeptical about the existence of such a factor. Modern studies of thrombopoietin begin with the cloning of c-mpl (the cellular counterpart of the v-mpl oncogene) and its cognate ligand genes. Following the cloning of the c-mpl proto-oncogene,2 Methia et al3 found that, in the presence of oligonucleotides antisense to the gene, CD34+ cells developed into megakaryocytic precursors less efficiently. As the development into other lineage was nearly intact, it was reasonably argued that the c-mpl protein may be the receptor for a thrombopoietin-like factor.3 This study inspired numerous investigations, which culminated in the cloning of the thrombopoietin gene in 1994.1, 4-8